2021
DOI: 10.5650/jos.ess20299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyvinyl Alcohol on Drug Release from Nanocomposite Particles Using Poly (L-lactide-<i>co</i>-glycolide)

Abstract: namic diameter of 1-3 μm are deposited minimally in the mouth and throat and maximally in the lung parenchymal regions, such as the alveolar or deep-lung region 5 . Thus, inhalable nanocomposite particles are a promising inhalation system. Furthermore, nanoparticles can overcome mucus clearance 6 . In addition to macrophages, they are also taken up by other cells such as cancer cells and epithelial cells 7 10 . These properties of nanoparticles are useful for drug delivery; however, the size of nanoparticles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“… 46 Among versatile types of surfactant used in NSs preparation, it is clear that PVA is widely used with a significant impact on the stability and physical features of drug-loaded nanoparticles including nanospheres and/or nanocapsules. 18 , 46 , 47 GPS has hydrophobic nature with limited aqueous solubility. 26 Increasing PVA concentration in the external aqueous phase supports GPS molecules to be tightly incorporated into PLGA core and minimum diffusion out to the external phase leading to higher entrapment efficiency ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 46 Among versatile types of surfactant used in NSs preparation, it is clear that PVA is widely used with a significant impact on the stability and physical features of drug-loaded nanoparticles including nanospheres and/or nanocapsules. 18 , 46 , 47 GPS has hydrophobic nature with limited aqueous solubility. 26 Increasing PVA concentration in the external aqueous phase supports GPS molecules to be tightly incorporated into PLGA core and minimum diffusion out to the external phase leading to higher entrapment efficiency ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different literature showed that the effect of PVA on release profile is basically concentration-dependent. 47 , 48 GPS is tightly incorporated with inner PLGA core and insoluble in an aqueous phase containing lower concentrations of PVA, below that is required for micellar formation and/or solubilizing GPS, 46 resulting in suppressing the initial burst of GPS out to release medium parallel with neglected effect on the total % cumulative release after three days. 47 , 48 Typical spheres of GPS-loaded PLGA nanoformulations demonstrated by transmission electron micrographs ensure that emulsion solvent evaporation method utilizing probe sonication could be considered an accessible and optimum technique could produce core /shell nanosystem.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of PVS, nanoparticles are also created that provide prolonged release of medicinal substances [21]. The effects of PVA on the release behavior of polymer nanoparticles from nanocomposite particles using amino acids were investigated [22]. PVA cross-linked microspheres are used in oral precision relief systems [23,24].…”
Section: Introductionmentioning
confidence: 99%